Radiation and Restoration; or, How Best to Make a Blight-Resistant Chestnut Tree. (10th February 2014) - Curry, Helen Anne
Abstract: This article charts the history of an unusual approach taken to restoring the American chestnut to its native range between 1955 and 1980. The chestnut, once abundant in the eastern United States, had been nearly wiped out by a blight to which it had little resistance. In 1955 the geneticist W. Ralph Singleton proposed that exposing chestnuts to radiation might produce trees carrying a genetic mutation for blight resistance. These could then be used to breed many more resistant trees, which would in turn be used for forest restoration. This effort undoubtedly originated in postwar atomic enthusiasm, yet as I argue here, it appealed for still other reasons, which explain why it persisted long after such enthusiasm had faded. Radiation-induced mutation offered a promising technological solution derived from recent genetics research that would address specific challenges of breeding blight-resistant chestnuts. In particular, it offered a speedy alternative to hybridization with Asian trees, a long process seen to diminish the desired qualities of the American chestnut and its integrity as a species. By exploring this confluence of nuclear technology, genetics, and species restoration, and placing it in the longer history of chestnut restoration efforts, this article highlights more broadly the challenges that emerge when saving a species requires significant human intervention and especially genetic manipulation.